PENGARUH PELATIHAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT DRACO INTERNASIONAL - Saepulloh, Acep; Ichwan Hamzah, Muhammad; Trisasmita, Rio (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The purpose of this study was to determine the effect of training, motivation, and job discipline of employees working on the performance at PT Draco Internasional. This study used the associative method and primary data. Data collected through questionnaires and interview which conducted on 55 employees of PT Draco Internasional. This study uses data analysis methods include validity test, reliability test, classic assumption test, multiple linear regression analysis, F test, t test and also the coefficient of determination test to test and prove the research hypothesis. Based on the result the following conclusion is obtained: Test results partially for training variable with statistic value tcount > ttable (8.859 > 2.021) and a probability value of 0.000 < 0.05, then Ho is rejected means there is influence significant from the training variable on employee performance. Partial test results for motivational variable with statistic value of tcount > ttable (3.483 > 2.021) and a probability value of 0.001 < 0.05, then Ho has rejected means that there is a significant effect of the motivation variable on employee performance. Partial test results for job discipline variable with a statistic value tcount > ttable (2.667 > 2.021) and a probability value of 0.010 < 0.05, then Ho has rejected means that there is a significant effect of the job discipline on employee performance. Simultaneous test results with a value of Fcount > Ftable (39.242 > 2.78) and a probability value of 0.000 < 0.05, then Ho is rejected or Ha is accepted which means there is a significant simultaneous influence (togetherness) of the training variable, motivation variable, and job discipline variable together on the employee performance variable. The amount of the adjusted coefficient of determination (adjusted R2) is 0.680 or 68%, which means that the independent variables can be explained in the employee performance variable by 68% while the remaining 32% is explained by other factors outside of this research.